Role of transformational leadership of primary health center heads in the success of the national immunization program: a qualitative study - Nawir Rahman (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: The National Immunization Program is a cornerstone of public health policy; however, variations in immunization performance persist at the primary health care level. Leadership at Primary Health Centers (Puskesmas) plays a crucial role in translating national policies into effective local implementation. Transformational leadership has been increasingly recognized as a potential mechanism for strengthening program performance, yet qualitative evidence from primary health care settings in low- and middle-income countries remains limited. This study aimed to explore the role of transformational leadership exercised by heads of Primary Health Centers in supporting the success of the National Immunization Program. Research Methodology: A qualitative descriptive–exploratory design was employed. In-depth, semi-structured interviews were conducted with 23 purposively selected informants, including heads of Primary Health Centers and health workers directly involved in immunization services. Data were analyzed using thematic analysis to identify key leadership-related mechanisms influencing program implementation. Results: Four interrelated themes emerged from the analysis: vision-oriented leadership, empowerment and motivation of health workers, team collaboration and coordination, and community engagement and trust building. Clear vision-setting by leaders aligned staff efforts with immunization targets, while supportive supervision and participatory decision-making enhanced health worker motivation. Effective teamwork facilitated adaptive problem-solving in response to operational challenges, and active community engagement strengthened public trust and acceptance of immunization services. Conclusion: The findings indicate that transformational leadership at the primary health care level supports successful immunization program implementation through integrated leadership practices that combine strategic vision, workforce empowerment, collaboration, and community engagement. Strengthening the capacity for transformational leadership among Primary Health Center heads may enhance the sustainability and effectiveness of national immunization programs in decentralized health systems.